ANALISIS KOMPETENSI PROFESIONAL GURU FISIKA TERHADAP PENGGUNAAN PERALATAN LABORATORIUM: STUDI KASUS DI SMAN 1 BEBESEN ACEH TENGAH - Annisa, Fera; Sabaruddin, Sabaruddin; Rahmawati, Rahmawati (Department of Physics Education, Faculty of Teacher Training and Education, UNIVERSITAS MA, 2024)
Professional competence is a qualification that supports teachers in teaching in the classroom. One aspect of this competence is teachers' ability to use laboratory equipment to support the learning process. This study employed a qualitative method to analyze the professional competence of physics teachers in using laboratory equipment at SMAN I Bebesen, Aceh Tengah. The research subjects consisted of five students and two physics teachers at SMAN I Bebesen, Aceh Tengah. Data were analyzed using the interactive model framework by Miles and Huberman. Instruments used included observation sheets, questionnaires for teachers and students, and interview guidelines. The results of data analysis showed variations in the professional competence of physics teachers in using laboratory equipment at SMAN I Bebesen, Aceh Tengah, viewed from several aspects. This study concludes that teachers' abilities in managing laboratories and utilizing the environment as a learning medium, planning practical-based learning, conducting practical learning, and authentic assessment of practical learning have been implemented well and in accordance with the learning needs. Factors supporting these results include teachers' educational background, teaching experience, preparation, participation in scientific activities, and ability to guide students' scientific work. Teacher professionalism directly influences the implementation of practical activities. When teachers have skills in managing and using laboratory equipment, it supports more effective practical implementation. Hopefully, this condition can increase student motivation and achieve satisfactory learning outcomes in practical activities.